FOREST DYNAMICS IN THE EASTERN AMAZON WITH SPECIAL REFERENCE TO SAPOTACEAE SPECIES - Pequeno Reis, Leonardo; Marques dos Reis, Pamella Carolline; Ruschel, Ademir Roberto; Macedo Silva, José Natalino; Pereira de Carvalho, João Olegário; Lopes de Souza, Agostinho; Hofmann Mota Soares, Marcio; Ninokata Miyahara, Roberto Koichi (Floresta, 2015)
Abstract Sapotaceae species are among the most dominant tree species in the Amazon forest and are high valued timbers. This paper aimed to evaluate the effect of Reduced Impact Logging (RIL) over a dense tropical rain forest with special reference to Sapotaceae species, to generate information helping decision making in forest management. In 1997, out of a 1050 ha forest area located in the municipality of Moju, State of Pará, Brazil, 200 ha were selected to be logged applying a logging intensity of 23 m3 ha-1 and RIL techniques. To monitor forest dynamics, 22 permanent sample plots (11 ha sampling area) were established and all trees with DBH ≥ 10 cm were measured in years 1995, 1998 and 2010. In the whole observation period, mortality and ingrowth of Sapotaceae species were, respectively, 1.5% year-1 and 1.0% year-1. Trees with full overhead light grew 0.39 cm year-1 and those completely shaded grew only 0.16 cm year-1. Mortality higher than ingrowth indicates that the population of Sapotaceae species still need a period longer than 13 years to recover equilibrium after RIL, despite showing increased diametric growth rates. Resumo Dinâmica de uma floresta no leste da Amazônia com ênfase às espécies de Sapotaceae. As espécies de Sapotaceae estão entre as mais dominantes na floresta amazônica e possuem alto valor comercial. O trabalho objetivou avaliar o efeito da Exploração de Impacto Reduzido (EIR) sobre uma floresta ombrófila densa com ênfase às espécies de Sapotaceae para gerar informações que possam subsidiar decisões a serem tomadas sobre o manejo de florestas nativas. De uma área florestal de 1.050 ha, situada no município de Moju, PA, foram selecionados 200 ha para EIR com intensidade de 23 m3 ha-1 em 1997. O monitoramento florestal foi feito com 22 parcelas permanentes (11 ha), sendo medidas todas as árvores com DAP ≥ 10 cm, nos anos de 1995, 1998 e 2010. No período total (1995 a 2010) a mortalidade das espécies de Sapotaceae foi de 1,5% ano-1 e o ingresso de 1,0% ano-1. As árvores com copas totalmente expostas à luz tiveram o incremento de 0,39 cm ano-1 e aquelas totalmente cobertas o incremento foi de 0,16 cm ano-1. A mortalidade maior que o ingresso indica que as espécies de Sapotaceae necessitam de um período maior que 13 anos para recuperar o equilíbrio após a EIR, apesar do aumento no crescimento diamétrico. Palavras-chave: Impacto pós-colheita; mortalidade; manejo florestal.